Increasing the Distance of Adjacent Palladium Atoms for Configuration Matching in Selective Hydrogenation. (17th November 2022) - Ge, Xiaohu; Cao, Yueqiang; Yan, Kelin; Li, Yurou; Zhou, Lihui; Dai, Sheng; Zhang, Jing; Gong, Xueqing; Qian, Gang; Zhou, Xinggui; Yuan, Weikang; Duan, Xuezhi
Abstract: Precisely tailoring the distance between adjacent metal sites to match adsorption configurations of key species for the targeted reaction pathway is a great challenge in heterogeneous catalysis. Here, we report a proof‐of‐concept study on the atomically sites‐tailored pathway in Pd‐catalyzed acetylene hydrogenation, i.e., increasing the distance of adjacent Pd atoms ( d Pd‐a‐Pd ) for configuration matching in acetylene semi‐hydrogenation against coupling. d Pd‐a‐Pd is identified as a structural descriptor for describing the competitiveness for reaction pathways, and the increased d Pd‐a‐Pd prefers the semi‐hydrogenation pathway due to simultaneously promoted C2 H4 desorption and the destabilized transition state of the C2 H3 * coupling. Spectroscopic, kinetics and electronic structure studies reveal that increasing d Pd‐a‐Pd to 3.31 Å delivers superior selectivity and stability due to energy matching and appropriate hybridization of Pd 4d with In 2s and, especially, 2p orbitals. Abstract : The distance between adjacent Pd atoms is theoretically and experimentally demonstrated to be significant for defining the reaction pathways for selective hydrogenation processes exemplified by acetylene semi‐hydrogenation here. Increasing the distance favors the formation of ethylene while restraining those of byproducts due to the simultaneously promoted C2 H4 desorption and destabilized transition state of C2 H3 * coupling.